Penerapan Sanksi Pidana dalam Pasal 504 Kitab Undang-Undang Hukum Pidana terhadap Pengemis di Kota Jambi - Wardani, Retno Kusuma; Yuneida, Setly Selva; Dari, Nayu Triska Wulan; Rani, Diana (Wajah Hukum, 2024)
The government has regulated the handling of beggars on public roads in accordance with Article 504 of the Criminal Code. However, not all beggars in Jambi City receive social rehabilitation from the Social Service, and until now no beggar has been subject to criminal sanctions. The aim of this research is related to the application of criminal sanctions in Article 504 of the Criminal Code against beggars in Jambi City. The research method used is a legal sociology approach so that the design of this activity is carried out over 6 months. The scope or object of this research is about the effectiveness of criminal sanctions against beggars on public roads so that the main materials and tools used are primary legal materials and secondary legal materials. The place used in this research was the city of Jambi and the data collection technique was used by direct interviews with the Jambi City Social Service so that the analysis technique was qualitative analysis. The results of the discussion of this research are that it has not been implemented by the Social Service, the Civil Service Police Unit, and the police due to a misunderstanding regarding the contents of Article 504 of the Criminal Code. This can be seen from the fact that there are still beggars at red light intersections, so fast and appropriate treatment is needed.